USE OF MICELLAR MOBILE PHASE FOR THE CHROMATOGRAPHIC SIMULTANEOUS DETERMINATION OF ATENOLOL AND INDAPAMIDE IN PHARMACEUTICAL DOSAGE FORM - SAVITA S YADAV; JANHAVI R RAO (International Journal of Pharma and Bio Sciences, 2012)
Rapid liquid chromatographic procedure has been developed for the simultaneous determination of Atenolol and Indapamide in a bulk drug and pharmaceutical formulation. The method uses C18 stationary phases and micellar mobile phases of 0.07M sodium dodecyl sulfate (SDS) pH 3 adjusted with phosphate buffer and 15% (v/v) 1- propanol as organic modifier and ultraviolet detection at 229 nm are used for the determination. Under these conditions, the studied indapamide and atenolol elute between 5.59 ± 0.10 and 8.058 ± 0.034 min at a 1.5 mL/min flow rate. Limits of detection are well below the concentrations of the drugs found in the commercial pharmaceutical preparation analyzed. The recoveries of the analytes in the pharmaceutical preparations are in the range 99.59 to 99.96% for atenolol and 99.03 to 99.14% for indapamide, respectively.